Dynamics of Femtosecond Pulsed Laser Induced Ti Plasmas under Different Pressures (Journal of Atomic and Molecular Sciences, 2015)
The femtosecond laser ablation process and induced breakdown spectroscopyof transition metal Ti in air background has been investigated systematically. The ablationprocess is simulated by means of a three-dimensional two temperature model(3D-TTM). The time-resolved spectroscopy is employed to determine the characteristicsof plasma during its evolution. The time-of-flight spectroscopy (TOFS) is alsoused to characterize the plasma expansion. The evolution behaviors of the plasma andits spectral characteristics have been analyzed as a function of pressure. It is shownthat the component, expansion behavior and characteristics of the plasma have strongpressure dependences. The results are discussed in terms of the interaction mechanismsbetween ambient air and plasma species.